ANALISIS REGRESI BERGANDA DENGAN METODE STEPWISE PADA DATA HBAT - Kondolembang, Ferry (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2011)
Multiple regression analysis as a statistical technique that can be used to analyze the relationship between a single dependent (respon) variable and several independent (peredictor) variables. Application for this analysis to be done specially in social economic. HBAT is a manufacture of paper products. Surveys of HBAT customer will be used to application multiple regression analysis in this paper to explain relationship satisfication between the other variables. Methods to selective entering and deleting among these variables until some overall criterion measure is achived. Objective methods for selecting variables that maximizes the prediction while employing the smallest number of variables. Results is the best model from multiple regression analysis is Y = -1.15106 + 0.36900 X6 - 0.41714 X7 + 0.31896 X9 + 0.17435 X11 + 0.77513 X12, means that customer satisfaction is significantly influenced by the complaint resolution, product quality, salesforce image, e-commerce activities, and product line. Besides that the assumptions in multiple regression analysis are met. SAS software has facility more complete than SPSS, Minitab, and R.